2015
DOI: 10.1542/peds.2014-2833
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound for the Diagnosis of Pneumonia in Children: A Meta-analysis

Abstract: BACKGROUND AND OBJECTIVE: Pneumonia is the leading cause of death of children. Diagnostic tools include chest radiography, but guidelines do not currently recommend the use of lung ultrasound (LUS) as a diagnostic method. We conducted a meta-analysis to summarize evidence on the diagnostic accuracy of LUS for childhood pneumonia. METHODS:We performed a systematic search in PubMed, Embase, the Cochrane Library, Scopus, Global Health, World Health Organization-Libraries, and Latin American and Caribbean Health S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
331
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(357 citation statements)
references
References 28 publications
17
331
3
6
Order By: Relevance
“…densities, or pleural effusion). A meta-analysis including 8 prospective studies performed in neonates and pediatric population and enrolling 765 children showed that LUS had an overall sensitivity of 95% (95%CI: 94-97), positive likelihood ratio of 15.3 and negative likelihood ratio of 0.06 for the presence of pneumonia as diagnosed based on clinical criteria and radiographic findings [8].…”
Section: Cp -mentioning
confidence: 99%
“…densities, or pleural effusion). A meta-analysis including 8 prospective studies performed in neonates and pediatric population and enrolling 765 children showed that LUS had an overall sensitivity of 95% (95%CI: 94-97), positive likelihood ratio of 15.3 and negative likelihood ratio of 0.06 for the presence of pneumonia as diagnosed based on clinical criteria and radiographic findings [8].…”
Section: Cp -mentioning
confidence: 99%
“…It is used to confirm endotracheal tube placement and for visualization of pneumothorax, alveolar pathologies, lung consolidation, and pleural effusion (7). Studies have shown that LUS is superior to direct radiographs in visualizing alveolar pathologies (3,4). Ultrasonography studies have been performed to visualize FBs located in different parts of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Posteroanterior (PA) and lateral chest radiographs should be performed when FB aspiration is suspected. Lung ultrasonography (LUS) is an alternative to direct radiographs in emergency departments to visualize lung pathologies (1)(2)(3)(4). In this case report, the visualization of aspirated foreign body (FB) and surrounding inflammation by LUS is described.…”
mentioning
confidence: 99%
“…In 2008 Copetti and Cattarossi published the first study reporting the high accuracy of lung ultrasound in detecting CAP in children [4] . Afterwards, several research teams with different expertise in ultrasounds confirmed the reproducibility of these results on different cohorts ofinpatients [5][6][7][8] Recently, current evidences have been included in a meta-analysis which further confirmed the high accuracy of ultrasound in the diagnosis of children pneumonia [9] As it appears, pediatricians may now choose between two imaging techniques. The question is: which is the best?…”
mentioning
confidence: 90%